A new variant of the ectodysplasin A receptor death domain gene associated with anhidrotic ectodermal dysplasia in a Turkish family and its simple diagnosis by restriction fragment length polymorphism - Rencuzogullari, Eyyup; Ezer, Banu Guven (Genes & Genetic Systems, 2023)
Ectodermal dysplasia (ED), which exhibits a wide range of clinical symptoms, may be classified into three major types: hypohidrotic, anhidrotic, and hidrotic. A male child (proband) showing anhidrotic dysplasia was used as the subject of this study. The biopsy of the big toe revealed that the male child had no sweat glands. Genetic analysis of the patient revealed a mutation caused by a homozygous nucleotide substitution in the EDAR-associated death domain (EDARADD) (rs114632254) gene c.439G>A (p.Gly147Arg). Phenotypically, his teeth were sharp, but eight teeth were missing (oligodontia). The patient had normal nails with dry skin, sparse hair, everted lower lip vermilion, hyperpigmented eyelids, and abnormal nasal bridge morphology around the eyes. There is also a homozygous dominant (healthy) female and a heterozygous male in this family, who are cousins (aunt children) to the heterozygous parents. The daughter of the patient was also heterozygous. This mutation represents homozygous recessive inheritance, which we describe for the first time. Furthermore, we demonstrated that this genetic disorder can be readily diagnosed using the restriction fragment length polymorphism (RFLP) method after digestion with MnII restriction endonuclease.